The Implementation of the Local Government Policy in the Tourism Sector in the Pujon Kidul Tourism Village, Malang - Tri Sutrisno; Cahyo Sasmito; Eri Yusnita Arvianti (IRDH International Journal of Social Sciences & Humanities, 2024)
Regional governments have the right to determine various public policies. The existence of policies intends to fight for the interests of society. Pujon Kidul Village is a tourist village which is a combination of unique, authentic, original, holistic and local elements. The original regional income obtained in this village is obtained from levies and tourism objects for Pujon Kidul Village and Malang Regency. This research aims to describe the implementation of local government policies in the tourism sector along with supporting and inhibiting factors, to improve community welfare in the Pujon Kidul Tourism Village, Malang. This research uses qualitative methods, with data analysis by Miles and Huberman. The results of this research show that policy implementation is determined by supporting factors, namely Malang Regency Regional Regulation Number 9 of 2022 concerning the Malang Regency Tourism Development Master Plan for 2022-2037. The inhibiting factors are the role of the Pujon Kidul village community which is not optimal in serving tourists, the Pujon Kidul village tourism management actors are also less professional in serving guests, the government's role is still not optimal in assisting tourism business actors, and there is no long-term planning for activities. tourist. Therefore, tourism assistance is needed.